Studi Kebijakan Pengembangan Produksi Biodiesel (Jarak Pagar) sebagai Bahan Bakar Alternatif di Sektor Industri dengan Menggunakan Sistem Dinamis - Siti Aisyah (JIEMS (Journal of Industrial Engineering and Management Systems), 2017)
This research has three objectives. The first objective is to develop a model of system dynamics of the production development of biodiesel as an alternative transportation energy source. The model is based on the National Model which was developed by Forrester. The second objective is to analyze the behavior of the model by using the policy instruments (depletion premium, loan interest, clean energy rules and sulfur tax) that support the effectiveness of the biodiesel production as an alternative transportation energy source. The third objective is to design the policy that support the effectiveness of the same system. The model has eight sub system: the biodiesel demand sub system in the transportation sector; biodiesel, Crude Jatropha Oil (CJO) and Jatropha curcas production sub system; population sub system; price sub system; capital goods sub system; petroleum income sub system; financial sub system; and government sub system. The model is then simulated in five policy scenario designs. The five scenarios were the ethanol production policy in year 2006 (basic model); the depletion premium fund raising percentage scenario; petroleum reserve raising scenario; price declining and production enlargement scenario; loan interest declining scenario. From the five scenarios, the best two scenarios were the petroleum reserve raising scenario and the price declining and production enlargement scenario. These two selected scenarios were then joined into two alternatives of policy that supported the effectiveness of the biodiesel production as an alternative transportation energy source. The first policy was the optimistic policy joining scenario and the second one was the pessimistic policy joining scenario.Keywords: System Dynamic, Biodiesel, Optimistic Policy, Pessimistic Policy.